Infrared thermography to locate impact damage in thin and thicker carbon/epoxy panels. Issue 7 (4th April 2017) - Boccardi, Simone; Carlomagno, Giovanni Maria; Boffa, Natalino Daniele; Ricci, Fabrizio; Meola, Carosena
Abstract : This work is concerned with the use of infrared thermography (IRT) to investigate impact damaging of carbon/epoxy materials. IRT has already proved suitability to visualize thermal effects induced by impact tests, but till now it has been mainly used with thin laminates with little attention toward the thicker ones. The aim of this work is to compare thermal effects evolving on both thin and relatively thick laminates to better validate the use of IRT and to get information useful for the comprehension of composites impact damaging mechanisms. Impact tests are carried out at different energies with a modified Charpy pendulum while the specimen surface opposite to that struck by the impactor is viewed by the infrared imaging device, which collects a sequence of thermal images. The analysis of the temperature variations during impact supplies information about the peak contact force, the initiation of the impact damage as well extension of delamination and of the overall impact affected zone. In addition, impacted specimens are non‐destructively evaluated with lock‐in thermography; the obtained phase images are compared with thermal images recorded during impact. An integration of results helps to estimate the impact damage location and its size. POLYM. ENG. SCI., 57:657–664, 2017. © 2017 Society of Plastics Engineers